2021
DOI: 10.1016/j.jtcvs.2019.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Aortic valve calcification: A new story with a twist?

Abstract: Schematic of the TWIST1/MATTL3 pathway in osteogenic differentiation of interstitial cells. CENTRAL MESSAGE A novel therapeutic target using the TWIST pathway and valvular interstitial cells may prevent aortic valve calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It has been reported that changes in RNA/DNA methylation and histone acetylation may have a role in the osteogenic differentiation of VICs. For example it was shown an interesting connection between VICs calcification and N6-methyladenosine (m 6 A) RNA-methylation via the upregulation of methyltransferase-like 3 (METTL3) and repression of the helix-loop-helix transcription factor TWIST ( 82 , 83 ), while in another study, methylation of the NOTCH-1 promoter was found to cause valve calcification through reduction of the NOTCH intracellular domain (NICD) activity and consequent increase of the Wnt/β-Catenin signaling causing enhanced expression of pro-calcific genes. Particularly interesting is the role of NOTCH-1 gene product in valve calcification in an epigenetic perspective.…”
Section: Epigenetic Regulation Relies On Metabolites Availabilitymentioning
confidence: 99%
“…It has been reported that changes in RNA/DNA methylation and histone acetylation may have a role in the osteogenic differentiation of VICs. For example it was shown an interesting connection between VICs calcification and N6-methyladenosine (m 6 A) RNA-methylation via the upregulation of methyltransferase-like 3 (METTL3) and repression of the helix-loop-helix transcription factor TWIST ( 82 , 83 ), while in another study, methylation of the NOTCH-1 promoter was found to cause valve calcification through reduction of the NOTCH intracellular domain (NICD) activity and consequent increase of the Wnt/β-Catenin signaling causing enhanced expression of pro-calcific genes. Particularly interesting is the role of NOTCH-1 gene product in valve calcification in an epigenetic perspective.…”
Section: Epigenetic Regulation Relies On Metabolites Availabilitymentioning
confidence: 99%
“…The importance of preventing calcification cannot be overemphasized, particularly for the longevity of aortic valve repair or reconstruction with or without patch material. 5 , 6 , 7 , 8 , 9 …”
mentioning
confidence: 99%
“… 10 , 11 Less immunogenic materials and improved processing methods have already been described to increase biocompatibility and to prevent an immunologic response to the xenogenic valve tissue. 9 , 11 It appears that a proper understanding of alpha-gal syndrome is important to improve the longevity of bioprosthetic material 13 , 14 , 15 , 16 , 17 in patients with a wide range of congenital and acquired heart disease.…”
mentioning
confidence: 99%